Correlation equation between physical and mechanical properties of sedimentary rocks - Zotsenko, Mykola; Vynnykov, Yuriy; Kharchenko, Maksym; Rybalko, Marina; Aniskin, Aleksej (Academic journal Industrial Machine Building Civil Engineering, 2022)
The results of parallel experimental studies of the physical and mechanical properties of sedimentary rocks of natural structure, including their penetration tests, are presented. The possibility of establishing empirical equations of the relationship between the physical (soil skeleton density and moisture content) and mechanical (specific resistance to penetration, angle of internal friction, specific adhesion, deformation modulus) characteristics of cohesive (on the example of light dusty loams of loess origin) and non-cohesive (on the example of fine sands, quartz) sedimentary rocks of natural structure is tested. It is noted that such equations are correct only for genetically identical types of sedimentary rocks
Keywords: sedimentary rock; penetration; humidity; specific penetration resistance; strength; deformation modulus; elationship